Feasibility of presidential proposals by candidates who aspire to the executive power in Colombia (2018)
The present investigation carries out a rigorous study of each presidential plan of the candidates that aspire to the executive power in the year 2018. In accordance with this, it is aimed to capture how viable is what each candidate for the presidency proposes, in order to give a concrete judgment of what it is more beneficial for the country in economic terms, fight against corruption and education. This study is based on the participation of a particular public (professors of the National University of Colombia, Bogotá campus, of the Faculties of Economic and Social Sciences). On the other hand, four important variables are taken into account for the analysis of the presidential plans by the respondents (viable, unfeasible, knows the candidate’s plan, does not know the candidate’s plan) to achieve covering all the information later presented and supported.